Hematological Changes in Nurses Handling Antineoplastic Drugs - M Ansari-Lari; M Saadat (Tehran University of Medical Sciences, 2002)
A cross-sectional study to determine whether occupational exposure to antineoplastic drugs can cause hematologic changes was performed. Blood samples were collected from a group of 24 hematology/oncology nurses who were exposed to antineoplastic drugs during a mean preiod of 5.5 years (standard error =1.1). The control group, matched by sex, and age, consisted of 18 nurses, worked on other sections. Within the normal range we found significant differences between the exposed and the control group in the absolute mean number of the total white blood cells (t=-2.50; df=40; P<0.05) and neutrophils (t=-1.72; df=40; P<0.05; one tailed test). The findings suggested, that the hematologic changes can serve as biological markers for medical surveillance and early detection of health problems due to handling antineoplastic drugs.